Fabrication of ceramic tube‐supported tetraethyl‐orthosilicate cross‐linked polydimethylsiloxane membranes for separation of furfural–water mixture by pervaporation technology. Issue 25 (23rd March 2022) - Lin, Tong Hoang; Toai, Phan Thi Danh; Tinh, Ninh Thi; Phat, La Nam; Huong, Le Minh; Viet, Nguyen Duc; Dat, Nguyen Minh; Nam, Hoàng Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, polydimethylsiloxane/tetraethyl‐orthosilicate (PDMS/TEOS) hybrid materials with different TEOS ratios were synthesized by cross‐linking method. Ceramic tube‐supported PDMS/TEOS membranes were fabricated by dip‐coating method. Effect of TEOS content, feed concentration, and feed temperature through separation of a furfural–water mixture by pervaporation (PV) technology was investigated. The highest PV performance was obtained with the total flux of 1.19 kg/m 2 h with TEOS content of 1.8 g, furfural feed concentration of 30 wt.%, operating temperature, and vacuum pressure at 100 kPa and 50 °C, respectively. PDMS/TEOS was successfully synthesized and coated on ceramic tube‐supported with a thickness of 15 μm. The ceramic tube‐supported membrane demonstrated good hydrophobicity with a contact angle of 109.5° and excellent thermal stability at 450 °C. The obtained results demonstrated that the ceramic tube‐supported PDMS/TEOS membrane is potent to be utilized for the separation of the furfural‐water mixture by PV technology. Abstract : Ceramic tube‐supported polydimethylsiloxane/tetraethyl‐orthosilicate (PDMS/TEOS) membranes with different precursor ratios were successfully prepared. The influences of various factors on the pervaporation (PV) performance of PDMS/TEOS are studied. The optimal PDMS/TEOS active layer demonstrated a good structural interaction between precursor, thermal stability, and hydrophobicity. Ceramic tube‐supported PDMS/TEOS membrane showed excellent PV performance of with low activation energy.